Why Does the Cortex Reorganize after Sensory Loss?. Issue 7 (July 2018) - Singh, Amy Kalia; Phillips, Flip; Merabet, Lotfi B.; Sinha, Pawan
Abstract : A growing body of evidence demonstrates that the brain can reorganize dramatically following sensory loss. Although the existence of such neuroplastic crossmodal changes is not in doubt, the functional significance of these changes remains unclear. The dominant belief is that reorganization is compensatory. However, results thus far do not unequivocally indicate that sensory deprivation results in markedly enhanced abilities in other senses. Here, we consider alternative reasons besides sensory compensation that might drive the brain to reorganize after sensory loss. One such possibility is that the cortex reorganizes not to confer functional benefits, but to avoid undesirable physiological consequences of sensory deafferentation. Empirical assessment of the validity of this and other possibilities defines a rich program for future research. Highlights: Neuroimaging studies have revealed that after loss of their primary sensory inputs, cortical areas often come to exhibit responses to inputs from other sensory modalities. These cortical changes are sometimes, but not always, accompanied by enhancements in behavioral abilities in the encroaching modalities, seemingly to compensate for the missing modality. We lack a comprehensive account of why cortical reorganization happens after sensory loss. Possibilities besides compensation include unmasking of dormant inputs, and mitigation of potentially harmful physiological changes in deafferented cortical tissue.